2015
DOI: 10.1160/th14-03-0251
|View full text |Cite
|
Sign up to set email alerts
|

Pro-thrombotic effect of exercise in a polluted environment: a P-selectin- and CD63-related platelet activation effect

Abstract: Exposure to diesel exhaust is an important cardiovascular risk factor and may promote atherothrombotic events. Some data suggest that polluted air exposure could affect haemostasis through platelet activation. The aim of the study was to investigate the effects of acute exposure to diesel exhaust on platelet activation and platelet function. We tested the hypothesis in a randomised, crossover study in 25 healthy men exposed to ambient and polluted air; 11 of the subjects also performed exercise during exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In experimental studies systolic 50 , 51 and diastolic 51 function decreased in response to PM2.5 exposure. Human studies suggested that circulating adhesion molecules VCAM-1, 37 , 38 ICAM-1, 36 , 38 E-selectin 39 and P-selectin 52 reflect a systemic inflammatory state and play a role in mediating the adverse cardiovascular effects of air pollution, subsequently leading to coronary heart disease 36 or increased susceptibility to thrombotic complications. 52 The evidence from these experimental 50 , 51 and human 36 39 , 52 studies justified our path analysis, focusing on circulating adhesion molecules, measured at the time of echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies systolic 50 , 51 and diastolic 51 function decreased in response to PM2.5 exposure. Human studies suggested that circulating adhesion molecules VCAM-1, 37 , 38 ICAM-1, 36 , 38 E-selectin 39 and P-selectin 52 reflect a systemic inflammatory state and play a role in mediating the adverse cardiovascular effects of air pollution, subsequently leading to coronary heart disease 36 or increased susceptibility to thrombotic complications. 52 The evidence from these experimental 50 , 51 and human 36 39 , 52 studies justified our path analysis, focusing on circulating adhesion molecules, measured at the time of echocardiography.…”
Section: Discussionmentioning
confidence: 99%
“…However, the return to T 0 gene expression levels at T 24 suggest that this cluster captures early changes in gene expression that restore to T 0 levels, at least by 24 hours. Although there was limited statistical enrichment for biological pathways within Cluster 2, genes such as BTNL are suggested to exacerbate asthma (Yamazaki, Goya et al 2010) and SELP expression/activity is a target for asthma therapy (Schumacher 2007, Takyar, Vasavada et al 2013) and associates with diesel exposure in other models (Wauters, Esmaeilzadeh et al 2015). Additional genes from Cluster 2 include F7 , a serum prothrombin conversion accelerator, that associates with enhanced disease risk associated with smoking (Redondo, Watzke et al 1999, Ben-Hadj-Khalifa, Lakhal et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, lower levels of phospholipid involved in the coagulation process, phostatidylcholine (PC), a component of the platelet-activating factor, were detected in ASMD type B organoids, which could relate to the coagulation problems associated with the disease. Furthermore, a significant reduction in the expression of the CD63 gene, a marker of blood platelet activation [ 49 ], was found in the ASMD type B liver organoids. The lack of CD63 expression has also been described in patients with Hermansky–Pudlak syndrome (HPS), which has hemorrhages due to platelet deficiency, among other symptoms [ 50 ].…”
Section: Discussionmentioning
confidence: 99%